Einstein, Neutrinos and the Palestinian State (AmeriQuests, 2011)
Albert Einstein may well be surprised to learn that neutrinos are apparently traveling faster than the speed of light, but he would be as surprised to learn that on the same day that discovery was announced, the Palestinian state finally moved towards formal recognition by the United Nations.
Keywords: Palestine Israel Einstein neutrinos